Implementasi Moderasi Beragama dalam Hubungannya dengan Sesama Muslim - Utomo, Budi; Ali, Mudzakkir; Hamzah, Ghufron (Cakrawala Journal is a scientific journal published by Nahdlatul Ulama Islamic Institute (IAINU) Kebumen. This journal focuses on the Islamic Education Management Study and Social Studies which is published twice a year.IAINU Kebumen, 2024)
This article aims to determine the implementation of religious moderation in relations with fellow Muslims. The research used is a qualitative research method with a type of library data collection by reading books, journals or other sources that are believed to be true. Indonesia is a country consisting of many tribes, races and religions, of course this easily creates divisions. Many of the divisions themselves originate from liberal and extremist ideologies that have entered Indonesia. As a multicultural nation, Indonesia is very appropriate to practice moderation. A moderate, fair and balanced mental attitude is the main key in managing diversity. The results of this discussion show that the implementation of religious moderation in relations with fellow Muslims includes: 1) Brotherhood with fellow Muslims; 2) Say hello and pray for each other; 3) Advise others wisely; 4) Maintaining the honor of fellow Muslims; 5) Respect elders, love younger ones; 6) Mingling with members of the opposite sex who are not mahram; 7) Do not hurt Muslim feelings; 8) Help each other with the affairs of fellow Muslims.